Consumer Confusion Choosing Me-Too Snack Packages: An Experimental Study (2016)
We hypothesize that (a) the presence of a leading brand next to a me-too brand and (b) the presence of the brand on the package prevents consumer confusion. This experimental design includes six categories of snacks (chocolate covered cake, waffle cookies, chocolate chip cookies, crackers, lollypops, and gummy candy); for each we estimate three logit models to determine the probability of (a) behavioral confusion, (b) cognitive confusion, and (c) overall confusion. Results support both hypotheses. Previous studies use cognitive rather than behavioral measures of confusion; we show that the three measures of confusion are complementary. Results yield important practical implications.